Economic efficiency of production of functional drinks based on pear pectin - Parpieva, G.; Soliev, M. (БНТУ, 2024)
This article discusses the advantages and economic efficiency of obtaining pectin extract from pear waste produced in Uzbekistan and the production of functional juice from its extract. It also presents the physicochemical characteristics of apple and pear juice produced with the addition of pear pectin extract. In addition, the cost and economic efficiency of juice production are substantiated by figures.